Peran Guru Pendidikan Pancasila dalam Menumbuh Kembangkan Budaya Sopan Santun Siswa Kelas VII-1 di SMP Negeri 1 Bulango Selatan - Susanti Ajunu; Roni Lukum; Asmun Wantu (Badan Penerbit STIEPARI Press, 2025)
This study aims to determine the role of Pancasila Education teachers in developing a culture of politeness in class VII-1 students at SMP Negeri 1 Bulango Selatan and to identify inhibiting factors in the process. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers have a central role as educators, mentors, and motivators in shaping students' character, especially related to polite behavior. However, this process still faces challenges, such as low student awareness, the negative influence of social media, and minimal support from the family environment. In conclusion, the role of teachers is very crucial in internalizing Pancasila values ​​in students' lives, and more innovative and collaborative strategies are needed with schools and parents to overcome existing obstacles.